2014
DOI: 10.3748/wjg.v20.i25.8292
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic ascites from spontaneous ectopic mesenteric varices rupture in NASH induced cirrhosis and successful outcome: A case report

Abstract: Bleeding from gastro-esophageal varices can often present as the first decompensating event in patients with cirrhosis. This can be a potentially life threatening event associated with a 15%-20% early mortality. We present a rare case of new onset ascites due to intra-abdominal hemorrhage from ruptured mesenteric varices; in a 37 years old male with newly diagnosed nonalcoholic steatohepatitis induced cirrhosis as the first decompensating event. The patient was successfully resuscitated with emergent evacuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The majority of studies (data sources) were conducted in the USA (n = 18, 58%), no more than 3 studies were conducted in any other country and in total; studies were conducted in 8 different mainly Western countries. Nine studies were specifically aimed at determining HRQoL 14,25,[27][28][29][30][31][32][33] ; 13 studies were focussed on specific related symptoms such as varices, pain or overall physical/mental symptoms [34][35][36][37][38][39][40][41][42][43][44] ; 2 were case studies each describing the experience of a single patient 45,46 ; 3 studies were concerned with PROM development and validation. [47][48][49] Within the identified studies, 1 was an opinion piece 50 ; 5 were conference abstracts 32,33,[42][43][44] and 5 were patient blogs/ stories.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies (data sources) were conducted in the USA (n = 18, 58%), no more than 3 studies were conducted in any other country and in total; studies were conducted in 8 different mainly Western countries. Nine studies were specifically aimed at determining HRQoL 14,25,[27][28][29][30][31][32][33] ; 13 studies were focussed on specific related symptoms such as varices, pain or overall physical/mental symptoms [34][35][36][37][38][39][40][41][42][43][44] ; 2 were case studies each describing the experience of a single patient 45,46 ; 3 studies were concerned with PROM development and validation. [47][48][49] Within the identified studies, 1 was an opinion piece 50 ; 5 were conference abstracts 32,33,[42][43][44] and 5 were patient blogs/ stories.…”
Section: Study Selectionmentioning
confidence: 99%
“…[47][48][49] Within the identified studies, 1 was an opinion piece 50 ; 5 were conference abstracts 32,33,[42][43][44] and 5 were patient blogs/ stories. [51][52][53][54][55] The majority of the studies (n = 19) specifically identified the inclusion of NASH-cirrhosis patients, 14,[28][29][30]33,[35][36][37][38][39][40][41]43,45,46,49,51,55,56 4 studies were assumed to refer to NASH-cirrhosis-these studies grouped 'other' liver disease aetiologies as 1 group 32,34,43,47 ; the final 7 studies 25,42,48,50,52-54 only referred to their target group as 'cirrhosis patients'.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a literature review of published cases, we identified eight previous case reports of hemoperitoneum in the setting of bleeding ectopic abdominal varices [3,[20][21][22][23][24][25][26]. Four patients underwent exploratory laparotomy with ligation with 100% mortality [21,[24][25].…”
Section: Discussionmentioning
confidence: 99%